2022
DOI: 10.3390/v14051078
|View full text |Cite
|
Sign up to set email alerts
|

Coxsackievirus A6 Recombinant Subclades D3/A and D3/H Were Predominant in Hand-Foot-And-Mouth Disease Outbreaks in the Paediatric Population, France, 2010–2018

Abstract: Coxsackievirus A6 (CVA6) emerged as the most common enterovirus of seasonal outbreaks of hand-foot-and-mouth disease (HFMD). We investigated CVA6 genetic diversity among the clinical phenotypes reported in the paediatric population during sentinel surveillance in France between 2010 and 2018. CVA6 infection was confirmed in 981 children (mean age 1.52 years [IQR 1.17–2.72]) of whom 564 (58%) were males. Atypical HFMD was reported in 705 (72%) children, followed by typical HFMD in 214 (22%) and herpangina in 57… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 47 publications
4
12
0
1
Order By: Relevance
“…Phylogenetic analysis revealed that the nt sequences from the 3Dpol region belonged to 23 bootstrap-supported clades (recombinant forms (RFs); A–X) in agreement with previous reports ( Figure 2 B) [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 43 , 44 , 45 , 46 , 47 ]. Most of the CV-A6/TH strains (84%, 147/174) in this study belonged to the previously described RF-A, while only ~6% (11/174) of the strains were assigned to RF-N (6%), and one strain was classified as RF-H (0.6%).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Phylogenetic analysis revealed that the nt sequences from the 3Dpol region belonged to 23 bootstrap-supported clades (recombinant forms (RFs); A–X) in agreement with previous reports ( Figure 2 B) [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 43 , 44 , 45 , 46 , 47 ]. Most of the CV-A6/TH strains (84%, 147/174) in this study belonged to the previously described RF-A, while only ~6% (11/174) of the strains were assigned to RF-N (6%), and one strain was classified as RF-H (0.6%).…”
Section: Resultssupporting
confidence: 93%
“…Over the past decade, an increase in the number of CV-A6 recombinant mutants has been reported [ 40 , 41 ]. To find evidence of recombination within the CV-A6 variants characterized in Thailand (CV-A6/TH strains) and the previously defined strains, 174 samples were analyzed using sequencing of their VP1 and 3Dpol regions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study also determined risk factors for adult HFMD which included a family size of 4 or more, having a child under 5 years of age, and having a child recently diagnosed with HFMD. These results support the human-to-human transmission of and why children may be affected more than adults [ 28 ].…”
Section: Methodssupporting
confidence: 75%
“…These include fever, anorexia, rashes, and joint pain. The difference in the clinical picture of this recent outbreak to other outbreaks of HFMD was the appearance of red blisters on skin, and can be due to a new variant of CV-A16 [ 28 ].…”
Section: Methodsmentioning
confidence: 99%